Effect of adjuvant chemotherapy on periosteal osteosarcoma: a systematic review. (28th April 2022) - Tsukamoto, Shinji; Righi, Alberto; Kido, Akira; Honoki, Kanya; Tanaka, Yuu; Fujii, Hiromasa; Mavrogenis, Andreas F; Tanaka, Yasuhito; Errani, Costantino
Abstract: Background and Objective: The effects of adjuvant chemotherapy on periosteal osteosarcoma are controversial. Therefore, we conducted a systematic review of studies comparing mortality, local recurrence, distant metastasis and secondary malignancy incidence among patients who underwent surgery and (neo-) adjuvant chemotherapy or surgery alone for periosteal osteosarcoma without distant metastases at diagnosis. Methods: Of the 210 studies identified in the search, 13 were included in this study, involving 291 patients with periosteal osteosarcoma in total. Results: The mortality rates in the surgery and (neo-) adjuvant chemotherapy and surgery alone groups were 11.3% (8/71) and 16.3% (16/98), respectively. The overall pooled odds ratio was 0.89 ( P =  0.800). The local recurrence rate in the surgery and (neo-) adjuvant chemotherapy group was 12.1% (8/66), while that in the surgery alone group was 17.6% (13/74). The overall pooled odds ratio was 1.31 ( P =  0.601). The distant metastasis rate in the surgery and (neo-) adjuvant chemotherapy group was 15.2% (10/66) and that in the surgery alone group was 10.8% (8/74). The overall pooled odds ratio was 1.51 ( P =  0.444). The incidence of secondary malignancy in the surgery and (neo-) adjuvant chemotherapy group was 7.6% (9/118) and that in the surgery alone group was 2.7% (2/74). The overall pooled odds ratio was 2.29 ( P =  0.187). Conclusions: Adjuvant chemotherapy did not appear to improve the prognosis of patients with periosteal osteosarcoma. No association was found between the use of adjuvant chemotherapy and development of secondary malignancies. Abstract : Adjuvant chemotherapy did not appear to improve the prognosis of patients with localized periosteal osteosarcoma. No association was observed between adjuvant chemotherapy use and the development of secondary malignancies.